2012
DOI: 10.3892/or.2012.1732
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional upregulation of HER2 expression in the absence of HER2 gene amplification results in cetuximab resistance that is reversed by trastuzumab treatment

Abstract: Abstract. The recent identification of HER2 gene amplification as a novel predictor of resistance to the EGFR (HER2)-targeted antibody cetuximab and of response to combination therapies against EGFR and HER2 in wild-type KRAS tumor settings may represent a further step toward personalized medicine for patients with colorectal cancer. Herein, we show that transcriptional upregulation of HER2 expression in the absence of HER2 gene amplification is a molecular phenomenon that takes place in EGFR-dependent, wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In preclinical models, lapatinib showed greater growth inhibition of TGFβ-activated colon cancer cells than antagonists targeting only ErbB1 or ErbB2 receptors [58]. Moreover, HER-2 amplification seems related to cetuximab resistance [36,59], suggesting that testing HER-2 inhibitors in HER-2 positive CRC population has a strong biological rationale. Actually, the combination of trastuzumab with either lapatinib or pertuzumab is being tested in a pioneer phase II study enrolling KRAS wild-type CRC patients harboring amplification of the HER-2 oncogene that have run out of options [60].…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical models, lapatinib showed greater growth inhibition of TGFβ-activated colon cancer cells than antagonists targeting only ErbB1 or ErbB2 receptors [58]. Moreover, HER-2 amplification seems related to cetuximab resistance [36,59], suggesting that testing HER-2 inhibitors in HER-2 positive CRC population has a strong biological rationale. Actually, the combination of trastuzumab with either lapatinib or pertuzumab is being tested in a pioneer phase II study enrolling KRAS wild-type CRC patients harboring amplification of the HER-2 oncogene that have run out of options [60].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that underlies this study is that cetuximab resistance may occur through the activation of alternate ErbB receptors. Recent efforts have highlighted the role of HER2 signaling as a targetable cetuximab resistance pathway[10,25]. Lapatinib, a small molecule inhibitor of EGFR and HER2, was evaluated as monotherapy in chemo-refractory colorectal cancer[26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The use of trastuzumab to inhibit HER2 in colorectal cancer was explored in a Phase II study in which enrollment was limited to patients with HER2 overexpression. The low rate of HER2 overexpression in colorectal cancer (observed in 8% of tumors in that trial) [10] resulted in poor enrollment although partial responses were observed in 5 of 7 evaluable patients[28]. Similarly, a Cancer and Leukemia Group B (CALGB) phase II trial of trastuzumab in combination with 5-fluoruracil, leucovorin and oxaliplatin in refractory patients showed some efficacy but again was limited by poor enrollment due to the low rate of HER2-overexpressing colorectal tumors[29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation